2021
DOI: 10.3390/app11178172
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Text Analysis Using Context-Aware Normalization of Social Media Informal Text

Abstract: We proposed an application and data variations-independent, generic social media Textual Variations Handler (TVH) to deal with a wide range of noise in textual data generated in various social media (SM) applications for enhanced text analysis. The aim is to build an effective hybrid normalization technique that ensures the use of useful information of the noisy text in its intended form instead of filtering them out to analyze SM text better. The proposed TVH performs context-aware text normalization based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Table 5 lists the number of correct, incorrect, and non-normalized words. These same 300 words were then put through the normalization methods proposed by [ 12 , 39 ]. Both these models were able to use the regular expression method and a spell-check algorithm to normalize OOV words with repeated letters resulting in impressive outcomes.…”
Section: Experimental Evaluation and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 5 lists the number of correct, incorrect, and non-normalized words. These same 300 words were then put through the normalization methods proposed by [ 12 , 39 ]. Both these models were able to use the regular expression method and a spell-check algorithm to normalize OOV words with repeated letters resulting in impressive outcomes.…”
Section: Experimental Evaluation and Resultsmentioning
confidence: 99%
“…Both these models were able to use the regular expression method and a spell-check algorithm to normalize OOV words with repeated letters resulting in impressive outcomes. Table 5 provides a comparison of the outcomes of the RBPsWRL- Sym model and that of the normalization models proposed by [ 12 , 39 ]. As seen in Fig 20 , the RBPsWRL-Sym model increased the F1 score from 78% and 81% to 88%.…”
Section: Experimental Evaluation and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach shows good performance for text normalization for Indonesian TTS with a Word Error Rate (WER) of 0.0805. Another study conducted by (Khan & Lee, 2021) concluded that In this research, it is proposed to develop an application called Textual Variations Handler (TVH), which is a generic application that works in a variation-independent manner to handle various types of noise in textual data originating from various social media (SM) applications to improve text analysis. The aim of this research is to introduce a hybrid normalization technique that is effective in ensuring that information obtained from noisy text data can be utilized in the desired form.…”
Section: Literature Reviewmentioning
confidence: 99%